Evaluasi Harga Jual Dengan Metode Cost Plus Pricing Pendekatan Full Costing Pada UMKM Saputra Snack Di Kota Bontang - Nita wulandari (Jurnal Administrasi Bisnis Fisipol Unmul, 2021)
This study aims to determine whether there is a difference in the calculation in determining the selling price between the UMKM Saputra Snack method with the cost plus pricing method with full costing approach and to know the selling price use the cost plus pricing method with full costing approach at the UMKM Saputra Snack can be able to competitive. The type of research is used quantitative. The research method used case study. The analysis technique used to calculation of the selling price using the cost plus pricing method with a full costing approach. The data used in this study are data on production costs and non-production costs during 2019. The results show that there are differences in setting the selling price because of the inaccuracy in treating cost components, namely the components of factory overhead costs such as equipment depreciation costs, production building depreciation, administrative costs, marketing costs in calculating the cost of goods manufactured which are used as the basis for determining the selling price. So that the calculation of the selling price with the cost plus pricing method, the full costing approach is greater than selling price of UMKM Saputra Snack. The results of the evaluation of the selling price of product using the cost plus pricing method of the full costing approach at UMKM Saputra Snack can still compete with similar products, because the selling price of similar products on the market is still high. Therefore, the results of the evaluation of the selling price of UMKM Saputra Snack's product are still reasonable and the selling price of the product can be increased so that it can increase the profit as expected.